DESKRIPSI PENERAPAN METODE CARD SORT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN ILMU PENGENTAHUAN SOSIAL - Gamar Al Haddar (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This study aims to find out the description of the application of card sort method in improving student’s learning motivation on social science subjects seen from the process of implementation in teaching and learning activities that is at the beginning of learning, in the core activities of learning and at the end of the learning process.This research is descriptive qualitative research. The instrument of this study is the researcher himself. Data collection techniques used includes (1) participant observation (2) interviews and (3) achievement test (4) study documents.The result of the research shows that the application of card sort learning’s model could increase the students' learning motivation. It can be seen from the following aspects below: (1) The students become more competent in their social, interaction, cooperation and courage in expressing their opinions (2) The students more enjoy the learning process. This is seen from the number of students who are actively asked to friends and teachers (3) the application of card sort method can make students become more independent in understanding the learning materials submitted by teachers. An aspect which is need to note that in using card sort method for learning process, it needs material arranged systematically, complete, and detail so that the indicators of the aim can be achieved.